Effect Of Cellulosic Material From Oil Palm Empty Fruit Bunches (Opefb) On The Reinforcement Properties Of Recycled Paper - Abdul Rahman, Khairul Hafizuddin (2017)
The use of recycled fibers in the Malaysian paper industry has been an economic and environmental necessity due to the limited availability of virgin fiber. However, with each recycling, the paper strength decreases, hence different methods are employed to increase its strength potentials. Various forms of oil palm cellulosic materials viz. OPEFB-UB. OPEFB-OZP, OPEFB-MCC and OPEFB-TEMPO were used to enhanced the strength properties of the recycled paper that were obtained from the old corrugated container (OCC).